2010
DOI: 10.2106/jbjs.i.00778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acquired Glenoid Bone Defects on Surgical Technique and Clinical Outcomes in Reverse Shoulder Arthroplasty

Abstract: Glenoid bone defects, when managed with an alteration of surgical technique, including bone-grafting when indicated, are not a contraindication to reverse total shoulder arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 21 publications
3
95
0
1
Order By: Relevance
“…19,20,25,37,43,47,49,50,70 Several techniques have been described to reconstruct severe bone loss of the glenoid, including staged revisions as well as the use of autografts and allografts. 1,2,4,7,12,13,19,41,52,53,54,55,68 All techniques have their inherent drawbacks, however, and no ideal approach to reconstruct severely deficient glenoids has so far been identified.…”
mentioning
confidence: 99%
“…19,20,25,37,43,47,49,50,70 Several techniques have been described to reconstruct severe bone loss of the glenoid, including staged revisions as well as the use of autografts and allografts. 1,2,4,7,12,13,19,41,52,53,54,55,68 All techniques have their inherent drawbacks, however, and no ideal approach to reconstruct severely deficient glenoids has so far been identified.…”
mentioning
confidence: 99%
“…Studies included in our review showed an overall mean improvement in ASES scores of 51.6 points (from 27.5 to 79.1), which, although not directly comparable, is greater than the improvement reported in RSA performed for cuff arthropathy (40.75) [46][47][48][49].…”
Section: Discussionmentioning
confidence: 49%
“…Baseplate malposition can occur very easily in these cases especially in cases that require large structural bone grafts to augment regions of eroded bone. Identification of an alternative centerline with the central post or screw directed towards the scapular spine is a method to improve baseplate fixation as well in cases of bone loss, but determination of this line intraoperatively can be challenging [36]. All of these potential complications encourage the surgeon to pursue all means necessary for safe and effective placement of the glenoid component in both standard and reverse total shoulder arthroplasty.…”
Section: Common Failure Mechanisms Of and Difficulties In Shoulder Armentioning
confidence: 99%